2019
DOI: 10.1002/cmdc.201900497
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Conjugation of a Chimeric BET Degrader Enables in vivo Activity

Abstract: The ability to selectively degrade proteins with bifunctional small molecules has the potential to fundamentally alter therapy in a variety of diseases. However, the relatively large size of these chimeric molecules often results in challenging physico‐chemical properties (e. g., low aqueous solubility) and poor pharmacokinetics which may complicate their in vivo applications. We recently discovered an exquisitely potent chimeric BET degrader (GNE‐987) which exhibited picomolar cell potencies but also demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 40 publications
8
144
0
Order By: Relevance
“…A deeper understanding of the stability of the TC will be crucial to achieve this, and may be quantified through techniques such as surface plasmon resonance (SPR), as recently demonstrated by Roy et al [55]. In particular, the researchers observed that TCs with long half-lives displayed enhanced cooperativities and more favourable degradation profiles in comparison to those with fast dissociation kinetics, a finding which has subsequently been validated by Pillow et al [165]. The use of biophysical techniques to monitor TC kinetics when optimising PROTAC linker chemistry may become more commonplace in future as a strategy to improve PROTAC potency and selectivity whilst mitigating the hook effect.…”
Section: Discussionmentioning
confidence: 92%
“…A deeper understanding of the stability of the TC will be crucial to achieve this, and may be quantified through techniques such as surface plasmon resonance (SPR), as recently demonstrated by Roy et al [55]. In particular, the researchers observed that TCs with long half-lives displayed enhanced cooperativities and more favourable degradation profiles in comparison to those with fast dissociation kinetics, a finding which has subsequently been validated by Pillow et al [165]. The use of biophysical techniques to monitor TC kinetics when optimising PROTAC linker chemistry may become more commonplace in future as a strategy to improve PROTAC potency and selectivity whilst mitigating the hook effect.…”
Section: Discussionmentioning
confidence: 92%
“…GNE-987 ( Fig. 2), containing a potent tetracyclic BRD4 inhibitor, exhibited extremely high activities in degradation of BRD4 and growth inhibition of acute myeloid leukemia EOL-1 cells in low pM levels [44]. Due to its poor pharmacokinetics (PK), GNE-987 was attached to an antibody of CLL1 (C-type lectin-like molecule-1) to form the conjugate CCL1-5 with good PK properties.…”
Section: Vhl-based Protacsmentioning
confidence: 99%
“…Although PROTAC technology was first described nearly 20 years ago 4 , there has been a dramatic increase in interest and activity catalysed by improvements in the embedded E3 ligase binders [5][6][7][8] which have delivered higher cell permeability. These improvements have increased cellular protein degradation potency of PROTACs from the high micromolar range to the low or even sub-nanomolar range [9][10][11][12] .…”
mentioning
confidence: 99%